2016
DOI: 10.1080/21624054.2016.1190900
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of chromatin segregation to the nuclear periphery inC. elegansembryos

Abstract: In eukaryotic organisms, gene regulation occurs in the context of chromatin. In the interphase nucleus, euchromatin and heterochromatin occupy distinct space during cell differentiation, with heterochromatin becoming enriched at the nuclear and nucleolar peripheries. This organization is thought to fine-tune gene expression. To elucidate the mechanisms that govern this level of genome organization, screens were carried out in C. elegans which monitored the loss of heterochromatin sequestration at the nuclear p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Recent studies, however, have called this model into question. In C. elegans, heterochromatin positioning at the nuclear periphery does not dictate gene silencing (Gonzalez-Sandoval and Gasser, 2016). Moreover, leveraging the model of rod cells with "inverted" nuclei, re-localization of heterochromatin from the periphery to the center of the nucleus has been found to alter neither gene expression nor chromatin organization (Falk et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies, however, have called this model into question. In C. elegans, heterochromatin positioning at the nuclear periphery does not dictate gene silencing (Gonzalez-Sandoval and Gasser, 2016). Moreover, leveraging the model of rod cells with "inverted" nuclei, re-localization of heterochromatin from the periphery to the center of the nucleus has been found to alter neither gene expression nor chromatin organization (Falk et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, however, suggest that the causality of the periphery-silencing relationship may be more complex, implying that there may be additional function(s) for peripherally-located HC. Indeed, in C. elegans , HC positioning at the nuclear periphery does not dictate gene silencing 17 . Moreover, leveraging the model of rod cells with “inverted” nuclei, re-localization of HC from the periphery to the center of the nucleus was found to neither alter gene expression nor chromatin organization at the 100s of kilobase to many megabase scale 18 .…”
Section: Introductionmentioning
confidence: 99%
“…LADs are enriched in histone H3 lysine 9 di-and trimethylation (H3K9me2/3) and this modification is also required for LAD recruitment to and maintenance at the nuclear lamina (Guelen et al 2008;Towbin et al 2012;Harr et al 2015). In mammals, proline-rich protein 14 (PRR14) has been shown to anchor these regions to the lamina through its interactions with heterochromatin protein 1 (HP1), a chromodomain protein that binds H3K9me3 (Poleshko and Katz 2014;Dunlevy et al 2020), while in Caenorhabditis elegans this function is carried out by the INM-bound chromodomain protein CEC-4 (Towbin et al 2012;Gonzalez-Sandoval et al 2015;Gonzalez-Sandoval and Gasser 2016;Harr et al 2016Harr et al , 2020Bian et al 2020). Intriguingly, heterochromatic regions have been shown to accrete due to phase separation directed by HP1α, and the organization of LADs at the lamina likely depends upon such biophysical forces (Larson et al 2017;Strom et al 2017;Falk et al 2019).…”
Section: Geographic Organization Of Lads Is Regulated By Chromatin Statementioning
confidence: 99%
“…LADs do not only have impacts on the local tethering of chromatin association to the nuclear periphery. LADs also affect the 3D structure of the genome through modifying interactions among topologically associating domains (TADs) [27,28,29]. Interestingly, an exhaustive study from van Steensel and colleagues has recently shown that many, but not all, repressed promoters in LADs are activated when moved to a more neutral chromatin environment [30].…”
Section: The Nuclear Envelope As Chromatin Organizermentioning
confidence: 99%